Influence of nutrient sources and weed control measures on weeds and yield of baby corn - Dhar, Niranjan Kumar; Dhar, Shiva; Kumar, Ashok (Annals of Agricultural Research, 2016)
A field experiment was conducted during kharif season of 2008 at the Experimental Farm of Division of Agronomy, Indian Agricultural Research Institute, New Delhi. The experiment was laid out in a factorial randomized block design and replicated thrice with the combination of 4 nutrient sources: 120-26.4-41.7 kg N-P-K/ha through fertilizers, 120 kg N through FYM, leaf compost and through vermicompost and 4 weed management practices: unweeded control, weed free check, two hand weeding at 20 and 40 days after sowing and application of atrazine @ 0.5 kg + pendimethalin @ 0.75 kg/ha tank mixed as pre-emergence (PE). The experiment was conducted on baby corn ’PEHM2’to study the effect of nutrient sources and weed control measures on weed control, nutrients removal by weeds, change in soil fertility and the economic returns. Result revealed that number of weeds and weed dry matter were unaffected by different sources of nutrients except in case of FYM application either with two hand weeding at 20 & 40 DAS or application of atrazine @ 0.5 kg + pendimethalin @ 0.75 kg/ha as PE. The number of monocot and dicot weeds and weed dry matter at both the stages were significantly higher in the unweeded control in comparison with remaining treatments, however, two hand weeding at 20 DAS and 40 DAS and application of atrazine @ 0.5 kg and pendimethalin @ 0.75 kg/ha as PE were remained at par.